Bedaquiline: a review of human pharmacokinetics and drug-drug interactions - van Heeswijk, R P G; Dannemann, B; Hoetelmans, R M W (Journal of antimicrobial chemotherapy, 2014)
Bedaquiline has recently been approved for the treatment of pulmonary multidrug-resistant tuberculosis (TB) as part of combination therapy in adults. It is metabolized primarily by the cytochrome P450 isoenzyme 3A4 (CYP3A4) to a less-active N-monodesmethyl metabolite. Phase I and Phase II studies in healthy subjects and patients with drug-susceptible or multidrug-resistant TB have assessed the pharmacokinetics and drug-drug interaction profile of bedaquiline. Potential interactions have been assessed between bedaquiline and first- and second-line anti-TB drugs (rifampicin, rifapentine, isoniazid, pyrazinamide, ethambutol, kanamycin, ofloxacin and cycloserine), commonly used antiretroviral agents (lopinavir/ritonavir, nevirapine and efavirenz) and a potent CYP3A inhibitor (ketoconazole). This review summarizes the pharmacokinetic profile of bedaquiline as well as the results of the drug-drug interaction studies.